Proton Acceleration by Io's Alfvénic Interaction. Issue 1 (17th January 2020) - Szalay, J. R.; Bagenal, F.; Allegrini, F.; Bonfond, B.; Clark, G.; Connerney, J. E. P.; Crary, F.; Ebert, R. W.; Ergun, R. E.; Gershman, D. J.; Hinton, P. C.; Imai, M.; et al.
Abstract: The Jovian Auroral Distributions Experiment aboard Juno observed accelerated proton populations connected to Io's footprint tail aurora. While accelerated electron populations have been previously linked with Io's auroral footprint tail aurora, we present new evidence for proton acceleration due to Io's Alfvénic interaction with Jupiter's magnetosphere. Separate populations were accelerated above the Io torus and at high latitudes near Jupiter. The timing suggests the acceleration is due to Alfvén waves associated with Io's Main Alfvén Wing. The inferred high‐latitude proton acceleration region spans 0.9–2.5 Jovian radii in altitude, comparable to the expected location for electron acceleration, and suggests the associated Alfvén waves are able to accelerate electrons and protons in similar locations. The proton populations magnetically connected to Io's orbit are recently perturbed, equilibrating with the nominal torus plasma population on a timescale smaller than Io's System III orbital period of ~13 h, likely due to wave‐particle interactions. The tail populations are split into a wake‐like structure with distinct inner and outer regions, where the inner region maps to an equatorial width nearly identical to the diameter of Io. The approximately symmetric surrounding outer regions are each slightly smaller than the central region and may be related to Io's atmospheric extent. The nominal, corotational torus proton population exhibits energization throughout all regions, peaking at the anti‐Jovian flank of the inner core region mapping to Io's diameter. These proton observations suggest Alfvén waves are capable of accelerating protons in multiple locations and provide further evidence that Io's Alfvénic interaction is bifurcated. Plain Language Summary: The interaction between Jupiter's moon Io and Jupiter's rapidly rotating magnetic field produces a persistent aurora in Jupiter's upper atmosphere. The Juno spacecraft's trajectory crossed magnetic field lines connected to this aurora. We found that protons are accelerated in multiple places between Jupiter and Io. The interaction is evidenced in two distinct regions, with the central core region mapping to almost exactly the size of Io in the equatorial plane. We also find the protons that comprise the nominal "background" population are hotter in this central region. Key Points: Three distinct populations of protons (10 eV to 50 keV) were observed connected to Io's auroral tail Alfvén waves accelerate protons both near the Io torus Alfvén boundary and at an altitude of 0.9–2.5 R J Io's Alfvénic interaction is split into two regions spanning multiple Io diameters wide downtail